A new Coelorinchus from the western Indian Ocean with comments on the C. tokiensis group of species (Teleostei: Gadiformes: Macrouridae) - Prokofiev, Artem M.; Iwamoto, Tomio (Zootaxa, 2023)
A new species, Coelorinchus zinjianus sp. nov., is described from the western Indian Ocean off Madagascar. In many respects, the new species is similar to C. quadricristatus but differs from that species in details of scale spinulation, mouth coloration (pale vs. dark), size of external light organ, and some other proportions. Together with C. flabellispinis and C. trunovi, these species form the flabellispinis species group, which is restricted to the northern and western Indian Ocean and is similar in most respects to the West-Pacific tokiensis group, but differs in the size and shape of the terminal snout scute (long and pointed, diamond-shaped vs. small and blunt) and apparently attaining a smaller adult size (< 45–55 cm TL vs. > 80–90 cm TL, depending on the species).